PERLINDUNGAN HUKUM BAGI SATGAS BATALYON GERAK CEPAT (BGC) TNI MONUSCO KONGO DALAM MISI PERDAMAIAN PBB - Oklim Ariana Elisabeth Kembau; Supri Abu (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2025)
In accordance with the Preamble to the 1945 Constitution, the Indonesian nation's aspiration to contribute to achieving world peace is inseparable from its participation in the UN peacekeeping mission. Indonesia's active international role in UN Peacekeeping Missions since 1957 has involved the deployment of thousands of Indonesian National Armed Forces (TNI) personnel, one of which is the TNI BGC Task Force. They carry out peacekeeping missions in the conflict-ridden Democratic Republic of the Congo, a mission area fraught with danger. To carry out their duties as ambassadors of world peace, they require definite legal protection. Based on the above background, the author raises two research questions in this paper. First, the legal status of the TNI Monusco Congo BGC Task Force in peacekeeping missions under national and international law. Second, the form of legal protection as a human right for the TNI Monusco Congo BGC Task Force in peacekeeping missions under national and international law. The research method used in this paper is qualitative, with a normative juridical legal approach. The author focuses on a statutory approach. Data collection was conducted through library research. Data analysis was conducted using qualitative analysis, which is a research procedure that produces descriptive data in the form of written words.Ultimately, this paper aims to examine and analyze in more depth the legal status of the BGC TNI Monusco Congo Task Force in peacekeeping missions based on national and international law. It also aims to identify and explain the forms of legal protection for human rights for the BGC TNI Monusco Congo Task Force in peacekeeping missions based on national and international law.